Prevalence of Hepatitis B in Healthy Population in Kupang City, East Nusa Tenggara, Indonesia - Irfan Irfan; Norma Tiku Kambuno; Irwan Budiana; Korri El Khobar (Global Medical & Health Communication (GMHC), 2022)
Hepatitis B virus (HBV) infection has remained a global health problem. Around 2 billion people worldwide are infected, and more than 257 million are categorized as chronic patients with a risk of developing progressive liver diseases, such as cirrhosis, liver failure, and hepatocellular carcinoma. In 2013, East Nusa Tenggara province had the most hepatitis B cases in Indonesia. Several factors cause a lack of information on HBV prevalence in the general population. First, they are inadequate disease surveillance systems with a high possibility of some acute and chronic infections being unreported. Second, geographical barriers to achieving suitable and sufficient data collection, considering the total population of 250 million people distributed in more than 17,000 islands. Third, the limited testing facilities for detecting chronic HBV resulted in many people being undiagnosed. This study was conducted to discover the prevalence of hepatitis B in healthy populations. It was a cross-sectional study with a random sampling method from April 2016 to March 2020 in Kupang city, East Nusa Tenggara. Subjects are prison inmates, pregnant women, primary school students, high school students, health workers, orphanage children, and families who live under the same roof with hepatitis B patients. We screened 11,152 subjects for HBsAg positivity using the ELISA and rapid detection tests. We found that 1,490 subjects (13.4%) were reactive to HBsAg. This HBsAg-positive prevalence stood far above the national rate of 7.1% in 2013, meaning that Kupang city is a region with high hepatitis B endemicity. Therefore, the local government should develop prevention strategies, diagnosis, post-infection management, and effective treatment, including mass vaccination programs for at-risk groups.